GENDER EQUALITY UNDER ISLAMIC FAMILY LAW (FEDERAL TERRITORIES) ACT 1984 - Nurulbahiah Binti Awang (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
It is claimed that Islamic family law is discriminatory against women in which women do not have similar rights with men. It is due to the misinterpretation on the concept of gender equality within only formal equality rather than substantive equality. The interpretation of gender equality without acknowledging sexual and cultural differences of people will probably discriminate against them. This study discusses the meaning of formal and substantive equality in which understanding it is imperative in understanding the concept of gender equality under Islamic Family Law (Federal Territories) Act 1984 (IFLA) . This study highlights on the provisions of IFLA in which it applies substantive equality to maintain gender justice. The provisions of IFLA relating to the different rights of Muslim women and men in marriage and family relations are analysed whether it is discriminatory against women. This study is a qualitative research in which, the data collected through reading and analysis of the previous research relating to the issues of gender equality. It also refers to the relevant statutes of law, report, cases and current issues relating to women’s rights. This study finds out that different entitlements of rights and duties between husband and wife under the provisions of IFLA are equal whenever both are equally responsible but not necessarily similar to fulfil the duties and responsibilities in a family institution. In addition to that, IFLA provides special measure considering women biological, physical and psychological nature and nurture. The measure is necessary to secure that women will get similar opportunity as men to enjoy their rights in private and public spheres. It is believed that IFLA through its universal attributes could be the best model governing the relationships between husband and wife which can be applicable not only for Muslim but also for non-Muslim in Malaysia with some amendment and modification through the methods of ijtihad which is not contrary with the substance principle of Shari’ah.